Psychometric properties of a questionnaire assessing the extent of integration in a problem-based learning curriculum - Marwan F. Abu-Hijleh (18780834) (2025)
Background Integrated curricula reinforce student learning and retention of relevant knowledge. At Qatar University and Arabian Gulf University medical colleges, Problem-Based Learning (PBL) is the principal teaching and learning strategy to implement integrated multidisciplinary system-based curriculum. In addition, other initiatives include integrated assessment, logical organization of teaching and learning methods, as well as combined faculty effort in curriculum planning and delivery. This multicenter study aims to develop and validate a questionnaire for measuring the extent of medical curriculum integration in PBL programs. Methods Following an extensive literature review, the content validity of a questionnaire was tested through focus group discussion with subject matter experts (n = 20), followed by pilot testing with medical students (n = 20). The content-validated questionnaire (31 items) was distributed to students in the two colleges. To examine the construct validity and construct reliability of the questionnaire, exploratory factor analysis (EFA) was conducted with 330 students followed by confirmatory factor analysis (CFA) on 579 students. Results EFA supported a four-factor structure of the questionnaire which explained 62% of the variance; however, four items were deleted because of low factor loading (< 0.5) or cross-loading on multiple factors. Further CFA also supported the four-factor structure. Another three items were removed due to high modification indices. The most parsimonious model consisted of 24 items with good fitness indices (χ2 = 512.23, df = 236, χ2/df = 2.17, CFI = 0.97, TLI = 0.97, RMSEA = 0.04, SRMR = 0.031, and AIC = 688.22). The four factors were: Planned Curriculum (3 items), Delivered Curriculum (10 items), Assessed Curriculum (4 items) and Learned Curriculum (7 items). The factor loadings of the items ranged from 0.61 to 0.84 with strong correlations between the four latent factors (constructs). The construct reliability of the total questionnaire was 0.97 and the four factors were between 0.94 and 0.97. In addition, there were strong significant correlations between curriculum integration scores and student satisfaction with the curriculum. Conclusions The developed questionnaire exhibits good evidence of construct validity and reliability. Further studies required to test the validity of this questionnaire in other settings. Other Information Published in: BMC Medical Education License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12909-025-07165-z